1983
DOI: 10.1128/iai.40.3.950-955.1983
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preformed antibody on the pathogenesis of experimental Candida albicans endocarditis

Abstract: The influence of preformed antibody on the induction of experimental Candida albicans endocarditis was investigated by both in vitro and in vivo techniques. Preincubation of C. albicans with immune serum (raised in rabbits by intravenous injection of Formalin-killed yeast cells) decreased adhesion to the constituents of nonbacterial thrombotic endocarditis, e.g., fibrin plus platelets, in vitro. Two different methods, with radiolabeled or viable yeast cells, were confirmatory and demonstrated decreased adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0
1

Year Published

1988
1988
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 38 publications
1
8
0
1
Order By: Relevance
“…Also, treatment of clots with free LTA blocked the adherence of the homologous and heterologous strains. These observations are similar to those reported earlier (10,21,22): decreased adherence of Candida albicans (O to 7.8% of control values; P < 0.001) and S. sanguis (40% of control values; P < 0.001) to the constituents of fibrin-platelet clots was reported when these organisms were preincubated with homologous rabbit immune sera. However, Adler et al (1) reported that rabbit antipneumococcal sera increased the in vitro adherence of pneumococci to fibrin-platelet surfaces (P < 0.001) and rabbit aortic valve cusps (P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Also, treatment of clots with free LTA blocked the adherence of the homologous and heterologous strains. These observations are similar to those reported earlier (10,21,22): decreased adherence of Candida albicans (O to 7.8% of control values; P < 0.001) and S. sanguis (40% of control values; P < 0.001) to the constituents of fibrin-platelet clots was reported when these organisms were preincubated with homologous rabbit immune sera. However, Adler et al (1) reported that rabbit antipneumococcal sera increased the in vitro adherence of pneumococci to fibrin-platelet surfaces (P < 0.001) and rabbit aortic valve cusps (P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that immunization elicited antibodies that hampered microbial attachment (27,29). We performed in vitro adherence assays to determine if polyclonal FimA antibodies interfered with bacterial adherence to vegetations.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on the effect of vaccination on susceptibility to experimental endocarditis. Immunizations with killed whole cells of Streptococcus sanguis, Streptococcus mutans, Streptococcus pneumoniae, Pseudomonas aeruginosa, nutritionally variant streptococci, and Candida albicans were protective against the development of endocarditis or early septicemia in rabbits (1,2,7,27,36). In contrast, anti-whole cell antibody did not protect rabbits from Staphylococcus aureus endocarditis (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of S. aureus endocarditis in animals is similar to that in humans (6), and the S. aureus inoculum needed to provoke endocarditis is relatively low (ϳ10 4 CFU per rat). In addition, antibody-mediated protection against the development of experimental infective endocarditis has been demonstrated for other microbial pathogens, including streptococci (1,11,43), Staphylococcus epidermidis (41), Pseudomonas aeruginosa (4), and Candida albicans (34). Two previous studies have examined the role of antibodies to staphylococcal surface antigens in protection against experimental endocarditis.…”
Section: Discussionmentioning
confidence: 99%